2014
DOI: 10.22206/cys.2014.v39i4.pp777-801
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de la morfología de la semilla de Pinus Occidentalis Swartz

Abstract: Resumen: La gran biodiversidad de especies de plantas en la isla La Española, hace conveniente la elaboración de trabajos que permitan identificar las familias, géneros y especies, a partir de diversos caracteres, como los anatómicos. En la República Dominicana se carece de investigaciones sobre las semillas de las especies endémicas. Es importante profundizar en estudios morfológicos y anatómicos de las semillas de nuestras especies y emplearlas con diferentes fines, como orientación taxonómica, conocer más s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…The plasticity results showed that smaller seeds had higher growth and development capacity than medium and larger seeds, so they have a greater ecological advantage as they can be widely distributed at different sites (Moles and Westoby, 2004), i.e., a higher value of root biomass indicates that seeds are more drought resistant (Olmo et al, 2014) and may have a better survival rate at sites with low moisture availability. However, these results differ from those reported by Miniño et al (2014), who elucidated that a large seed would give a larger seedling with a higher probability of survival as compared to a smaller one. For the stem dry biomass, Q. variabilis recorded lower values (18.56 to 29.78) compared to pine species (35.04 to 43.03) recorded by Flores et al (2018) using the same phenotypic plasticity index.…”
Section: Results and Discusioncontrasting
confidence: 99%
“…The plasticity results showed that smaller seeds had higher growth and development capacity than medium and larger seeds, so they have a greater ecological advantage as they can be widely distributed at different sites (Moles and Westoby, 2004), i.e., a higher value of root biomass indicates that seeds are more drought resistant (Olmo et al, 2014) and may have a better survival rate at sites with low moisture availability. However, these results differ from those reported by Miniño et al (2014), who elucidated that a large seed would give a larger seedling with a higher probability of survival as compared to a smaller one. For the stem dry biomass, Q. variabilis recorded lower values (18.56 to 29.78) compared to pine species (35.04 to 43.03) recorded by Flores et al (2018) using the same phenotypic plasticity index.…”
Section: Results and Discusioncontrasting
confidence: 99%
“…The morphological variables and the physical characteristics analyzed of the seed in Taxus globosa Schltdl. allowed to establish significant differences between geographical regions (Ramírez-Sánchez et al, 2011). Miniño Mejía et al (2014 analyzed the variability between populations of Pinus occidentalis Swartz based on morphological characteristics of the seed, while the external characteristics of the seeds allowed to identify different levels of variation in Bombacopsis quinata (Jacq.)…”
Section: Resultsmentioning
confidence: 99%